2005
DOI: 10.1165/rcmb.2004-0202oc
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Decreases Cellular ATP Demand and Inhibits Mitochondrial Respiration of A549 Cells

Abstract: Hypoxia inhibits activity and expression of transporters involved in alveolar Na reabsorption and fluid clearance. We studied whether this represents a mechanism for reducing energy consumption or whether it is the consequence of metabolic dysfunction. Oxygen consumption (JO2) of A549 cells and primary rat alveolar type II cells was measured by microrespirometry during normoxia, hypoxia (1.5% O2), and reoxygenation. In both cell types, acute and 24-h hypoxia decreased total JO2 significantly and reoxygenation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 41 publications
(42 reference statements)
4
54
1
1
Order By: Relevance
“…Inhibition of mitochondrial function by prolonged anoxia and subsequent recovery in the presence of Cd was concurrent with elevated levels of oxidative DNA lesions in Cd-exposed oysters. These changes are reminiscent of the typical mitochondrial alterations induced by intermittent oxygen deficiency in hypoxia-sensitive organisms, such as mammals (1,29,37,52,77), and suggest that Cd exposure may lead to the loss of the stress-resistant mitochondrial phenotype in oysters. Earlier studies showed that Cd can inhibit mitochondrial ETC and matrix enzymes and induce elevated rates of ROS generation in oysters (12,33).…”
Section: Discussionmentioning
confidence: 89%
“…Inhibition of mitochondrial function by prolonged anoxia and subsequent recovery in the presence of Cd was concurrent with elevated levels of oxidative DNA lesions in Cd-exposed oysters. These changes are reminiscent of the typical mitochondrial alterations induced by intermittent oxygen deficiency in hypoxia-sensitive organisms, such as mammals (1,29,37,52,77), and suggest that Cd exposure may lead to the loss of the stress-resistant mitochondrial phenotype in oysters. Earlier studies showed that Cd can inhibit mitochondrial ETC and matrix enzymes and induce elevated rates of ROS generation in oysters (12,33).…”
Section: Discussionmentioning
confidence: 89%
“…Our fi nding of intracellular ATP levels ( ‫ف‬ 3 mM) that are close to the K m of choline kinase for ATP ( ‫ف‬ 1.5 mM) ( 24 ) suggests that decreases in ATP levels in hypoxic cancer cells could also contribute to reduction in choline phosphorylation, an effect that could compound with changes in choline kinase expression and activity. In cells under moderate hypoxic stress, there are mechanisms that maintain ATP levels in a range that keeps the cell viable (25)(26)(27). This is usually done by coordinating various energy-supplying and energy-consuming processes.…”
Section: Discussionmentioning
confidence: 99%
“…A major factor in cell survival under low oxygen conditions is the ability of cells to increase glycolysis in order to maintain sufficient ATP levels [7,39]. Anoxia induced mild cell injury in both epithelial and microvascular endothelial cells, while 1 and 7 % oxygen was tolerated by both cell types.…”
Section: Discussionmentioning
confidence: 99%